2020
DOI: 10.1177/0969733020948115
|View full text |Cite
|
Sign up to set email alerts
|

Older people’s perceived autonomy in residential care: An integrative review

Abstract: Autonomy has been recognised as a key principle in healthcare, but we still need to develop a consistent understanding of older people’s perceived autonomy in residential care. This study aimed to identify, describe and synthesise previous studies on the perceived autonomy of older people in residential care. Ethical approval was not required, as this was a review of published literature. We carried out an integrative review to synthesise previous knowledge published in peer-review journals in English up to Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 70 publications
(382 reference statements)
1
65
0
1
Order By: Relevance
“…In our analysis, this happened as the arrangement of VM equipment and guiding practices pushed the client to ask for help, which has been recognised as a potential threat for situational autonomy in residential care. 6 Situating the equipment and medicine closer to each other eliminated the problem of simultaneous engagement in interaction and medicine taking (Extract 2). Furthermore, compared to straightforward guiding, the stepwise approach portrays the client as a knowledgeable participant who thus has more time to locate the medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our analysis, this happened as the arrangement of VM equipment and guiding practices pushed the client to ask for help, which has been recognised as a potential threat for situational autonomy in residential care. 6 Situating the equipment and medicine closer to each other eliminated the problem of simultaneous engagement in interaction and medicine taking (Extract 2). Furthermore, compared to straightforward guiding, the stepwise approach portrays the client as a knowledgeable participant who thus has more time to locate the medicine.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 For instance, the care practices that drive older adults to ask for help have been recognised as potential risks for client autonomy in residential care for older adults. 6 On the other hand, respecting others' rights to determine their own course of action has been found to enhance client autonomy. [7][8][9][10][11][12] This is achieved, for example, by using suggestions rather than straightforward orders in care work 9 and taking into consideration the guided person's ability to comply with the directions.…”
Section: Introductionmentioning
confidence: 99%
“…A welfare state can facilitate ageing in place by ensuring adequate income, suitable housing options, access to services and social support within and outside of the home [ 53 ]. It is equally important to ensure autonomy within the context of residential care in terms of people’s decisions about their daily activities, maintaining dignity and upholding human rights [ 54 , 55 ]. Welfare state support is especially important in relation to high support needs.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived low autonomy is also associated with basic education (< 6 years), slightest or no social support, anxiety, cognitive deterioration, low educational level and limitations in ADL [24]. It is noteworthy that older adults' perceived autonomy can be affected by different factors some of which are unchangeable such as educational level or marital status while other factors like physical and mental health, mobility and skills as well as self-efficacy are components on which interventions could be focused on [43]. In addition, our study revealed some other interesting associations.…”
Section: Discussionmentioning
confidence: 99%